2018
DOI: 10.1186/s12943-018-0758-4
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine and epigenetic control of CAF-induced metastasis: the role of HOTAIR stimulated by TGF-ß1 secretion

Abstract: BackgroundThe communication between carcinoma associated fibroblasts (CAFs) and cancer cells facilitate tumor metastasis. In this study, we further underlying the epigenetic mechanisms of CAFs feed the cancer cells and the molecular mediators involved in these processes.MethodsMCF-7 and MDA-MB-231 cells were treated with CAFs culture conditioned medium, respectively. Cytokine antibody array, enzyme-linked immunosorbent assay, western blotting and immunofluorescence were used to identify the key chemokines. Chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(135 citation statements)
references
References 40 publications
4
131
0
Order By: Relevance
“…In breast cancer, cancer‐associated fibroblasts (CAF) transcriptionally activate HOTAIR through the direct binding of SMAD2/3/4 to the HOTAIR promoter region. Then, HOTAIR epigenetically represses CDK5RAP1, stimulating CDK5 signaling and inducing EMT . PVT1 acts as competing endogenous RNA (ceRNA) for miR152, activating Hedgehog signaling and promoting EMT in hepatic stellate cells and thereby contributing to liver fibrosis .…”
Section: Long Non‐coding Rna and Tumor Plasticitymentioning
confidence: 99%
“…In breast cancer, cancer‐associated fibroblasts (CAF) transcriptionally activate HOTAIR through the direct binding of SMAD2/3/4 to the HOTAIR promoter region. Then, HOTAIR epigenetically represses CDK5RAP1, stimulating CDK5 signaling and inducing EMT . PVT1 acts as competing endogenous RNA (ceRNA) for miR152, activating Hedgehog signaling and promoting EMT in hepatic stellate cells and thereby contributing to liver fibrosis .…”
Section: Long Non‐coding Rna and Tumor Plasticitymentioning
confidence: 99%
“…71 Several recent studies have reported that CAFs-secreted TGF-β promotes cancer metastasis via regulation of lncRNA expression. 72,73 CXCL14 high CAFs upregulated LINC00092, which directly binds to PFKBP2 and promotes metastasis of ovarian cancer by altering glycolysis. 74 These findings suggest that modulation of CAF-derived signals by targeting lncRNAs could serve as a novel therapeutic strategy.…”
Section: Lncrnas In Tumor Microenvironmentmentioning
confidence: 99%
“…Activated fibroblasts are also producers of cytokines, chemokines, metabolites, enzymes, and ECM . Several recent studies have reported that CAFs‐secreted TGF‐β promotes cancer metastasis via regulation of lncRNA expression . CXCL14 high CAFs upregulated LINC00092, which directly binds to PFKBP2 and promotes metastasis of ovarian cancer by altering glycolysis .…”
Section: Molecular Mechanism Of Lncrnas In Cancer Metastasismentioning
confidence: 99%
“…Loss of TP53 in stromal fibroblasts has also been shown to promote breast tumor development in vivo through the production of SDF-1 (Addadi et al, 2010). Additional reported mechanisms include the altered expression in CAFs of non-coding RNAs and microRNAs (Verghese et al, 2013;Shah et al, 2015;Ren et al, 2018). Other components of the tumor microenvironment, including tumor-associated macrophages, have been implicated in tumor promotion through the expression of TFEB (Fang et al, 2017).…”
Section: Ube2tmentioning
confidence: 99%